Determinação multirresíduo de agrotóxicos em tabaco empregando método QuEChERS modificado e UHPLC-MS/MS - Abreu, Herliana Damelys Flores (2022)
Tobacco is the most widely grown non-food crop in the world, a wide variety of substances are used in it during and after its cultivation to protect it from pests, diseases and regulate its growth. Therefore, it is necessary to monitor the residues of these pesticides in tobacco in order to guarantee the safety of consumer products manufactured with it. However, the sample matrix contains an abundant amount and variety of sugars, waxes, resins, acids, etc., requiring a sample preparation step capable of reducing the presence of these substances that can interfere with the analysis of the compounds of interest. In this work, different modifications of the QuEChERS method, a low temperature precipitation step and different sorbents for cleaning tobacco extract were evaluated, including d-SPE sorbents like chitosan, fluorinated phase, Florisil®, Z-Sep+, EMR-lipid, C18, PSA, GCB, MWCNTs-OH, MWCNTs-COOH and SPE cartridge like PSA/GCB, LC-NH2 and Captiva EMR-lipid. The method established and validated in this work consisted of an extraction of QuEChERS citrate, followed by 1 h of freezer (-25 to -18 °C), cleaning of the extract by d-SPE with 150 mg MgSO4 + 10 mg MWCNTs-OH and finally a 5 times dilution with water and filtration of the final extract for analysis by UHPLC-MS/MS. The validation results were satisfactory, achieving recoveries between 70 and 120% and RSDs ≤ 20% for 74 compounds present in the CORESTA of 2021. The curves were prepared in the matrix extract due to the presence of a significant matrix effect for most analytes. LOD and LOQ values, despite the matrix complexity, were between 0.007-0.045 and 0.025-0.15 mg kg-1 respectively. The proposed method proved to be adequate for the multiresidue determination of pesticides in tobacco, achieving the detection of 9 of the 74 pesticides validated during the analyses of the real samples, this is two herbicides, five fungicides and two insecticides.